Melanotické paraneurony - Bednár, B (Ceskoslovenska patologie, 1990)
Histogenetic scheme of three germ layers causes difficulties in explanation of some tumorous structures derived from different classes. A conception of paraneurons concedes (besides "central" neuroectodermal paraneurons) a possibility of their local origin. The idea anticipates a broader phylogenetic ability of divergent differentiation of single extraneural cells. Paraneuronal theory used in oncology can explain local origin of some presumable combination variants of tumours, e.g. carcinoid type paraneuromas with melanin pigmentation. Substantial frequency of such tumours eliminates possibility of random coincidence and argues for ranging "peripheral melanin system" among paraneurons.
Keywords: Chromaffin System; melaniny; Humans; chromafinní systém; germinální a embryonální nádory; Neoplasms, Germ Cell and Embryonal; Melanins; lidé